The development of environmental crime and sanctions in Malaysia - Mustafa, Maizatun; Mohamed, Nurah Sabahiah (2014)

(untitled)
Environmental crime can be considered as a perpetration of harms against the environment and human health that violate the law. Thus, it differs considerably from the traditional criminal model that focuses on crimes against persons and private property. For this and other reasons, environmental crime would take longer to be accepted as a genuine category of crime as compared with other crimes. In Malaysia and elsewhere, environmental crimes continue to increase and extend to diverse areas including pollution, waste disposal, threats to flora, fauna and biodiversity, and illegal logging. Such increase requires the application of law on these crimes including providing criminal sanctions for actions that cause harm to the environment. Over the years, Malaysia’s changing perceptions about environmental vulnerability, and the consequences of environmental crimes on the quality of the environment has helped altered the view on environmental crime. At present various strategies have been introduced to deal with different types of environmental offences, with laws that target not only individual offenders, but also make provision for corporate liability. This paper discusses in general the scope of environmental crimes in Malaysia, and examines shifts in the regulation of environmental crime over the years since the passage of the Environmental Quality Act in 1974, identifying the development of innovative strategies within the law in dealing with these crimes. It also discusses the application of new mechanisms such as environmental forensics in assisting environmental law to detect, prevent or prosecute environmental crime. The purpose of this paper is to document changes within the law on environmental crime that have shaped criminal law and environmental protection in Malaysia.